2019
DOI: 10.1002/pros.23875
|View full text |Cite
|
Sign up to set email alerts
|

AKR1C3 expression in primary lesion rebiopsy at the time of metastatic castration‐resistant prostate cancer is strongly associated with poor efficacy of abiraterone as a first‐line therapy

Abstract: Background Previous studies had demonstrated that aldo‐keto reductase family 1 member C3 (AKR1C3), a crucial enzyme in the steroidogenic pathway, played an important role in abiraterone (ABI)‐resistance in metastatic castration‐resistant prostate cancer (mCRPC) by increasing intratumoral androgen synthesis. However, its value in predicting treatment response in patients with mCRPC is unknown. Method and Materials Data of 163 patients with metastatic prostate cancer between 2016 and 2018 were retrospectively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Several biomarkers have been identi ed to guide the treatment decision making for mCRPC patients, e.g. AR-V7, ARK1C3, neuroendocrine differentiation and etc (17)(18)(19). The positivity of these markers indicates poor prognosis in AR-targeting treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several biomarkers have been identi ed to guide the treatment decision making for mCRPC patients, e.g. AR-V7, ARK1C3, neuroendocrine differentiation and etc (17)(18)(19). The positivity of these markers indicates poor prognosis in AR-targeting treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As both AKR1C3 expression and AR-V7 expression were increased in rebiopsy specimens at mCRPC compared with initial diagnosis in our previous study, 11 we further investigated the correlation between AKR1C3 and AR-V7 in CRPC tissues. As shown in Table 1…”
Section: Positive Correlation Between Akr1c3 and Ar-v7 In Crpc Tissuesmentioning
confidence: 91%
“…Indeed, AKR1C3 expression in CRPC tissues is strongly associated with poor efficacy of abiraterone as a first-line therapy. 11 In addition, AKR1C3 has been shown to play different roles in mCRPC, such as acting as an EMT driver or AR coactivator. 10,21 Our previous studies revealed that AKR1C3 could act as a novel EMT driver to facilitate PCa metastasis through ERK signalling, which indicated a poor prognosis of patients.…”
Section: The Ar-v7/akr1c3 Complex Represses the Transcription Of B4mentioning
confidence: 99%
See 1 more Smart Citation
“…Ten or more separate studies have replicated the finding that AKR1C3 is overexpressed in CRPC [38,39,[70][71][72][73]75,76] . One such study showed AKR1C3 overexpression in primary lesion re-biopsies at the time of metastatic disease [77] . Consecutive prostate cancer specimens revealed increased AKR1C3 expression during progression to CRPC [78] .…”
Section: Hsd3b1 Genementioning
confidence: 99%